Geological study in Tal - Talekhu section of Manang District along the Besisahar – Chame Road - Luitel, Prakash; Panthee, Suman (Bulletin of the Department of Geology, 2020)
The section between Tal to Talekhu of Manang District lacks the detailed geological study. The geological mapping in the scale of 1:50,000 followed by the preparation of geological cross-section and lithostratigraphic column has been done in the present study. The studied area lies partially in the Higher Himalayan Crystalline and the Tibetan Tethys Sequence. The units of the Higher Himalayan Group from Tal to Talekhu consists mainly of vigorous to faintly calcareous gneiss, migmatitic gneiss, quartzite, granite, etc. They are named as the Calc. Silicate Gneiss and Paragneiss and the Orthogneiss and Granite units. The lowermost part of the Tibetan Tethys consisted of metamorphosed calcareous rocks containing silicates and feldspar, so this unit is termed as the Marble and Calc. Gneiss. The section is about 9 km in thickness and is highly deformed with presence of igneous rocks at many places.